The Relevance of Cognitive Aspects in the Educational Process in Primary School - Leoni, Chiara; Papa, Lucia (Formazione & insegnamento, 2022)
An analysis of the current situation in Italian schools shows an increase in the number of students with special educational needs, in particular specific learning disabilities and students with other diverse types of dysfunctions, and also a significant growth in early school leaving. The scenario that emerges underlines the need to modify the educational dynamics, adapting them to the specific needs of each student. This article describes how constructs such as Vygotsky's Zones of Actual and Proximal Development and Feuerstein's cognitive functions can provide an extremely useful perspective for the analysis of the cognitive processes of each student, favoring a personalized approach to classroom work. In 2006, the European Parliament first introduced the concept of key competences. The fifth competence, "learning to learn", places the gradual development of students' fragile or deficient cognitive functions as one of the fundamental objectives of schooling. The thesis of the present article is that the use of Feuerstein's Instrumental Enrichment in class can provide an effective approach for the improvement of students' cognitive functions, which can later be generalized to disciplinary learning.